PENGARUH TIPE LUAPAN LAHAN PASANG SURUT PADA LAHAN PADI TERHADAP SIFAT KIMIA TANAH ALLUVIAL DI DESA PARIT KELADI KECAMATAN SUNGAI KAKAP KABUPATEN KUBURAYA - Maya, Tino Asripin (Fakultas Pertanian Universitas Tanjungpura, 2019)
ABSTRACT This study aims to find out information about the chemical properties of alluvial soils and provide suggestion for rice fertilization for farmers. This research was conducted in Parit Keladi Village, Kakap River District, Kubu Raya District. This research was conducted in November - December 2018 on 3 types tidal overflow, Each type tidal overflow with type A, type B and type C, aech type overflow taken from the soil sample at a depth of 0-20 cm at 5 observation points and composite. The results showed that on the site soil had acidic pH, moderate to high N-total, low phosphorus, low potassium, medium to high C-organic, moderate to low CEC, low base saturation, low bulk density, and no salt content, gut water level and no pyrite content at the study site. The study site has a low bulk density type A 0.43, type B 0.73 and type C 0.79. Fertilizer advice N, P, K at type A (415 kg urea / ha, 14 kg SP36 / ha and 50 kg KCl / ha), at type B (171 kg urea / ha, 50 kg SP36 / ha and 50 kg KCl / ha) and type C (180 kg urea / ha, 79 kg SP36 / ha and 50 kg KCl / ha). Keywords: Alluvial Soil, Chemical Properties, Type of tidal landfill